The reliability-based evaluation of casing collapsing strength and its application in marine gas reservoirs. (March 2018) - Zhu, Xiaohua; Liu, Biao
Abstract: The casing serving in the marine gas reservoir is often squeezed by the collapse pressure from salt rock creeps. The combined action of acid corrosion media and high temperature result in necking deformation and even fracture. However, it is difficult the traditional design method of casing safety factor to deal with the randomness of the structural and load factors. The designed strength is either too high or too low. To face the challenges, the reliability evaluation method for the casing collapsing strength in marine gas reservoirs is developed based on the standard of collapsing strength and the load-strength interference model. The distribution of casing collapsing strength is firstly simulated by Monte Carlo sampling. The reliability calculation model of casing under different working conditions is obtained. Then, the quantitative relationship between the target reliability and the safety factor is explored by backward derivation. Four kinds of casing used in marine gas reservoir are evaluated. The result shows that the collapsing strength obeys a Gaussian distribution. The bigger the variation coefficient of casing parameters, the more dispersed the strength distribution. Based on the failure probability, the target reliability can be set and the safety factor can be calculated. The collapse pressure from creep is a key factor to control reliability. With the change of layer groups, the load distribution curve is gradually close to the intensity distribution curve until the interference failure occurs. The reliabilities of casings in some layer groups are < 50%. The corrosion defects and temperature are important factors to casing strength. The reliability and the life expectancy are greatly reduced with time, which leads to premature failure of some casings. Highlights: The reliability evaluation is developed based on the load-strength interference model. The reliability calculation model of casing under different working conditions is obtained. The collapse pressure from creep is a key factor to control reliability. The corrosion defects and temperature are important factors to casing strength.